2018
DOI: 10.1002/ijc.31396
|View full text |Cite
|
Sign up to set email alerts
|

Garlic intake and gastric cancer risk: Results from two large prospective US cohort studies

Abstract: Although many case-control studies suggested that garlic intake may reduce gastric cancer risk, evidence from prospective cohort studies has been lacking. We examined the association between garlic intake and subsequent risk of gastric cancer among 77,086 women in the Nurses' Health Study (1984-2014) and 46,398 men in the Health Professionals Follow-Up Study (1986-2014). Relative risks (RRs) and 95% confidence intervals (95% CIs) were estimated using Cox proportional hazards models. We additionally examined ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 37 publications
(59 reference statements)
1
28
0
Order By: Relevance
“…Table displays the characteristics of the included studies. A total of 18 studies with 142 921 subjects (5123 cases) published from 1989 through 2018 were identified, of which 15 were case‐control studies (4573 cases), 1 was case‐cohort study (152 cases), 1 was cohort study (292 cases), and 1 was randomized controlled study (106 cases) . Six of these studies were conducted in China, 2 in Sweden, 2 in Iran, 1 in Italy, 1 in South Korea, 1 in Lithuania, 1 in Netherlands, 1 in Turkey, 1 in Uruguay, 1 in the United States, and 1 in Venezuela.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table displays the characteristics of the included studies. A total of 18 studies with 142 921 subjects (5123 cases) published from 1989 through 2018 were identified, of which 15 were case‐control studies (4573 cases), 1 was case‐cohort study (152 cases), 1 was cohort study (292 cases), and 1 was randomized controlled study (106 cases) . Six of these studies were conducted in China, 2 in Sweden, 2 in Iran, 1 in Italy, 1 in South Korea, 1 in Lithuania, 1 in Netherlands, 1 in Turkey, 1 in Uruguay, 1 in the United States, and 1 in Venezuela.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, a total of 13 studies with 4889 participants investigated the association between garlic intake and H. pylori (Table ), 10 of which did not found a significant result. Six studies were conducted in Asia (3 in China, 2 in Iran, and 1 in Japan), 6 were in Europe (3 in Turkey, 1 in Bulgaria, 1 in Germany, and 1 in the United Kingdom), and 1 was in the United States.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations